Perceptions Toward Internet-Based Delivery of Hearing Aids among Older Hearing-Impaired Adults - Chandra, Navshika; Searchfield, Grant D. (Journal of the American Academy of Audiology, 2016)
Background: Despite evidence that hearing aids can improve the social and psychological functioning of older hearing-impaired adults, hearing aid uptake is low. High cost of hearing aids and poor access to audiology services in rural areas are potential barriers to hearing aid acquisition. Methods of hearing aid delivery deviating from the traditional clinician-based model have been available to consumers for many years. One such method is Internet hearing aid sales. However, research exploring Internet-based hearing aid delivery, as a method to improve hearing aid uptake in this population, is limited.Purpose: The purpose of this study was to explore the perceptions of older hearing aid users (aged ≥65 yr) toward Internet-based hearing aid delivery.Research Design: A qualitative approach was adopted to investigate older adults’ perceptions of buying hearing aids online.Study Sample: The sample consisted of 18 participants aged between 64 and 81 yr. Fourteen men and four women participated in this study. Participants were all experienced hearing aid users.Data Collection and Analysis: Face-to-face semistructured interviews were conducted. An interview schedule guided the interview. Interviews were recorded with a voice recorder and transcribed verbatim. Thematic analysis of the data was carried out.Results: Seven main themes emerged from the data. A general lack of awareness, but willingness to learn more about Internet hearing aid sales, was found. Two perceived benefits of Internet-based hearing aid delivery were identified: lower cost of hearing aids and greater convenience or physical accessibility. Numerous concerns and limitations were communicated. Concerns regarding the availability of clinical procedures, such as hearing tests, obtaining the correct-sized earmolds, and fine-tuning of hearing aids, were expressed. Participants conveyed distrust in online retailers. However, trust in and a preference for audiologists’ expertise, which was not perceived to be available online, was found. Participants further conveyed a preference for face-to-face contact. Finally, in this sample, a general lack of familiarity and confidence in using the Internet was communicated.Conclusions: Internet sales of hearing aids is a controversial topic in audiology. Although Internet-based delivery of hearing aids was perceived by older adults to be potentially beneficial, several shortcomings and concerns were conveyed. Irrespective of opinion of the role of Internet sales, audiologists should consider the opinions of the elderly as to how different service models may improve hearing aid uptake.
Keywords: aged; audiology; hearing aids; hearing loss; Internet